Pentoxifylline mitigates renal glycoxidative stress in obese mice by inhibiting AGE/RAGE signaling and increasing glyoxalase levels - Inacio, Maiara Destro [UNESP]; Costa, Mariana Campos [UNESP]; Lima, Tayra Ferreira Oliveira [UNESP]; Figueiredo, Ingrid Delbone [UNESP]; Motta, Bruno Pereira [UNESP]; Spolidorio, Luís Carlos [UNESP]; Assis, Renata Pires [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Baviera, Amanda Martins [UNESP] (Elsevier, 2020)
Aim: The pharmacological properties of pentoxifylline have been re-evaluated, particularly in chronic kidney disease in diabetes, favored by its anti-inflammatory action. Definitive evidences of renal outcomes are lacking, which indicates the need for investigation of novel mechanisms of action of pentoxifylline. We postulated that components associated with the metabolism of advanced glycation end products (AGEs) may be modulated by pentoxifylline, which consequently decreases the detrimental effects of obesity on kidneys. Main methods: C57BL-6J mice were fed a high-fat diet for 14 weeks and treated with 50 mg/kg pentoxifylline during the last 7 weeks. Changes in the renal levels of AGE metabolism-associated components were investigated, with particular focus on the receptor for AGEs (RAGE), its downstream components, and components related to AGE detoxification, including glyoxalase 1 (GLO 1). Key findings: Pentoxifylline reduced body weight gain, improved insulin sensitivity and glucose tolerance, downregulated biomarkers of glycoxidative stress, and enhanced plasma paraoxonase 1 activity. In the kidneys, pentoxifylline inhibited glomerular expansion, lipid deposition, reduced pro-inflammatory cytokine levels, and induced the activation of AMP-activated protein kinase. Pentoxifylline inhibited the renal accumulation of AGEs and reduced the levels of RAGE and its downstream components, and consequently mitigated oxidative stress and apoptosis. Pentoxifylline also increased the renal levels of GLO 1 and the activities of antioxidant enzymes. Urinary albumin levels were observed to be lowered, which reconfirmed the antialbuminuric effects of pentoxifylline. Significance: The novel mechanisms of action help explain the renoprotective effects of pentoxifylline and the attenuation of obesity-associated renal complications related to glycoxidative stress.
Keywords: Advanced glycation end products; Kidney; Obesity; Oxidative stress; Pentoxifylline; Phosphodiesterase inhibitors